The Mediating Role of Work Environment in the Relationship between Visionary Leadership and Employee Performance: Evidence from Public Health Offices in West Java, Indonesia - Abdulah Mubarok Dadang; Imas Purnamasari; Disman Disman; Janah Sojanah (Yayasan Darussalam Bengkulu, 2026)
Background: Digital transformation in Indonesian public health governance has placed new demands on employee performance at District/City Health Offices. Despite growing evidence on leadership-performance linkages, the specific mechanism through which visionary leadership shapes employee performance via work environment in Indonesian public health organizations remains empirically underexplored. This study investigates the mediating role of work environment in the relationship between visionary leadership and employee performance. Method: This quantitative cross-sectional study surveyed 180 Standard Minimum Service program managers across 27 District/City Health Offices in West Java Province using proportionate stratified random sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.0, testing three hypotheses regarding visionary leadership, work environment, and employee performance relationships. Results: All three hypotheses were supported. Visionary leadership demonstrated a very strong direct effect on work environment (β=0.916, t=43.512, p=0.000), and work environment significantly influenced employee performance (β=0.439, t=2.854, p=0.016). The indirect mediation path was significant (β=0.402, t=2.798, p=0.005), confirming full mediation. The direct effect of visionary leadership on performance was not significant (β=0.183, p=0.239), establishing that work environment is the necessary conduit for leadership's performance impact. Conclusion: Visionary leadership increases employee performance exclusively through the creation of a conducive work environment, not through direct supervision. Health office leaders should prioritize investments in technology infrastructure, collaborative organizational climate, and supervisor support systems. These findings align with Islamic management principles of amanah (trustworthiness), tabligh (communicative vision), and ta'awun (mutual cooperation).